Efektivitas Bakteri Tahan Salin dan Pemberian Batuan Fosfat terhadap Pertumbuhan dan Produksi Kedelai di Tanah Salin - Khoirotul Mutmainah; Eny Fuskhah; Endang Dwi Purbajanti (Agrosains : Jurnal Penelitian Agronomi, 2022)
The purpose of this study was to examine the effect of Rhizobium sp. and phoshate solubilizing bacteria and the application rock phosphate to the growth and production of soybean plants in saline soils. The methods used was Completely Randomized Design 4 x 3 with 3 replications. The first factor is treatment of Rhizobium sp. and phosphate solubilizing bacteria saline-resistant (CFU 109 cells/g) at 4 levels, F0 : 0 mg/pot, F1 : 10 mg/pot, F2 : 20 mg/pot, and F3 : 30 mg/pot. The second factor is doses of rock phosphate with 3 levels, B0: 0 kg/ha, B1: 50 kg/ha, and B2: 100kg/ha. The results showed that the inoculation of Rhizobium sp. and phosphate solubilizing bacteria saline-resistant were not significantly different on the N uptake parameters of seeds. Treatment with different doses of rock phosphate had no significant effect on all parameters. Inoculation of Rhizobium sp. and phosphate solubilizing bacteria and rock phosphate have not been able to significantly increase the growth and production of soybean varieties Anjasmoro in highly saline growing media with EC 6,26 dS/m, although there is a trend to increase soybean production.